A New Personalized Cooling Protocol to Activate Brown Adipose Tissue in Young Adults - Martinez-Tellez, Borja; Sanchez-Delgado, Guillermo; Garcia-Rivero, Yolanda; Alcantara, Juan M. A.; Martinez-Avila, Wendy D.; Muñoz-Hernandez, Maria V.; Olza, Josune; Boon, Mariëtte R.; Rensen, Patrick C. N.; Llamas-Elvira, Jose M.; Ruiz, Jonatan R. (Frontiers in Physiology, 2017)
Brown adipose tissue (BAT) activity is induced when humans are exposed to cold. Therefore, cold exposure prior to the 18F-FDG-PET/CT scan is used as a tool to quantify BAT. Several cooling protocols, including fixed and personalised ones are currently in use. The aim of the present study was to determine the effect of a new personalised cooling protocol where the shivering threshold was measured on a separate day, on BAT volume and activity in young adults. A total of 47 adults (n=28 women) aged 22±2 years participated in the study. We determined participants’ shivering threshold (visually and self-reported) using a water perfused cooling vest in an air-conditioned cold room. 48-72 hours later, participants wore the cooling vest set at 4ºC above the shivering threshold for 60 minutes prior to injection of 18F-FDG and 5ºC above the shivering threshold for 60 minutes after injection, until PET/CT scan. We quantified BAT following BARCIST 1.0 recommendations. We identified 40 participants (85%, n=25 women) as PET+ and 7 (n=3 women) as PET-. The PET+ group presented significantly higher BAT volume and activity than PET- group (all P<0.05). PET+ women had higher BAT mean activity than PET+ men (SUVmean: 5.0±1.6 vs. 3.6±0.9 g/ml respectively, P=0.003), and there were no significant sex differences in BAT volume (P=0.161). A total of 9 out of 47 participants did not shiver during the shivering threshold test. Our findings are similar to previous cold-stimulated human BAT studies; therefore, we conclude that our personalised cooling protocol is able to activate BAT in young adults.